Antimicrobial activity and inhibition of the NorA efflux pump of Staphylococcus aureus by extract and isolated compounds from Arrabidaea brachypoda. (March 2020) - de Sousa Andrade, Leila Maria; de Oliveira, Aylla Beatriz Melo; Leal, Antonio Linkoln Alves Borges; de Alcântara Oliveira, Felipe Araújo; Portela, Ana Lurdes; de Sousa Lima Neto, José; de Siqueira-Júnior, José Pinto; Kaatz, Glenn William; da Rocha, Cláudia Quintino; Barreto, Humberto Medeiros
Abstract: Arrabidaea brachypoda is a native shrub of the Brazilian Cerrado widely used in the folk medicine for treatment of renal diseases and articular pains. This study aimed to, first, evaluate the antimicrobial activity of both extracts and isolated molecules Brachydins BR-A and BR-B obtained from the flowers of A. brachypoda against Staphylococcus aureus, Escherchia coli and Candida albicans species. A second objective was to investigate if these natural products were able to potentiate the Norfloxacin activity against the strain Staphylococcus aureus SA1199-B that overexpress the norA gene encoding the NorA efflux pump. Extracts and isolated compounds were analyzed by HPLC-PDA and LC-ESI-MS respectively. Minimal inhibitory concentrations of Norfloxacin or Ethidium Bromide (EtBr) were determined in the presence or absence of ethanolic extract, dichloromethane fraction, as well as BR-A or BR-B by microdilution method. Only BR-B showed activity against Candida albicans . Addition of ethanolic extract, dichloromethane fraction or BR-B to the growth media at sub-inhibitory concentrations enhanced the activity of both Norfloxacin and EtBr against S. aureus SA1199-B, indicating that these natural products and its isolated compound BR-B were able to modulate the fluoroquinolone-resistance possibly by inhibition of NorA. Moreover, BR-B inhibited the EtBr efflux in the SA1199-B strain confirming that it is a NorA inhibitor. Isolated BR-B was able to inhibit an important mechanism of multidrug-resistance very prevalent in S. aureus strains, thus its use in combination with Norfloxacin could be considered as an alternative for the treatment of infections caused by S. aureus strains overexpressing norA . Graphical abstract: Image 1 Highlights: BR-B showed antimicrobial activity against Candida albicans (161 μg/mL). BR-B potentiated the activity of Norfloxacin against SA1199-B. BR-B also was able to modulate the resistance to EtBr against SA1199-B. BR-B caused intracellular accumulation of EtBr behavioring as a NorA inhibitor.